Financial integration between Indonesia and its major trading partners - Abdul Karim, Bakri; Abd. Majid, M. Shabri; Abdul Karim, Shamsul Ariffin (2009)
This study examines stock market integration among the emerging stock market of Indonesia and its major trading partners (Japan, the US, Singapore and China). We employ the newly proposed autoregressive distributed lag (ARDL) approach to cointegration and recent weekly stock market data spanning from July 1998 to December 2007. The results indicate the Indonesian stock market is cointegrated with the stock markets of the US, Japan, Singapore and China. Thus, this implies that the opportunities for international investors to gain benefits from international portfolio diversification in those markets are limited. In addition, any development in Japan, the US, Singapore and China markets should be considered by the Indonesia government in making policies regarding to the stock market of Indonesia.